Effects of Li+ conduction on the capacity utilization of cathodes in all-solid-state lithium batteries - Wang, Zhiping; Song, Shipai; Jiang, Chunzhi; Wu, Yongmin; Xiang, Yong; Zhang, Xiaokun (Frontiers in Chemistry, 2023)
Li+ conduction in all-solid-state lithium batteries is limited compared with that in lithium-ion batteries based on liquid electrolytes because of the lack of an infiltrative network for Li+ transportation. Especially for the cathode, the practically available capacity is constrained due to the limited Li+ diffusivity. In this study, all-solid-state thin-film lithium batteries based on LiCoO2 thin films with varying thicknesses were fabricated and tested. To guide the cathode material development and cell design of all-solid-state lithium batteries, a one-dimensional model was utilized to explore the characteristic size for a cathode with varying Li+ diffusivity that would not constrain the available capacity. The results indicated that the available capacity of cathode materials was only 65.6% of the expected value when the area capacity was as high as 1.2 mAh/cm2. The uneven Li distribution in cathode thin films owing to the restricted Li+ diffusivity was revealed. The characteristic size for a cathode with varying Li+ diffusivity that would not constrain the available capacity was explored to guide the cathode material development and cell design of all-solid-state lithium batteries.